1983
DOI: 10.1007/bf00213783
|View full text |Cite
|
Sign up to set email alerts
|

Projection patterns of different types of antennal sensilla in the antennal glomeruli of Drosophila melanogaster

Abstract: Cobalt fills from small, defined regions of the antenna in D. melanogaster show that the three types of sensilla on the third segment, the flagellum, and a fourth sensillum located in the arista, project into the glomeruli of the antennal lobe. We have identified 19 glomeruli in each lobe, according to their location, shape, and size. At least ten of these represent major projection areas of flagellar or aristal sensilla. The large majority of glomeruli is innervated from both antennae, but a small group of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(72 citation statements)
references
References 32 publications
4
67
1
Order By: Relevance
“…3E). These include IR75d (VL1), consistent with previous cobalt backfill analyses (Stocker et al, 1983), and the IR40a axons innervating the column but not most of the arm (Fig. 3E).…”
Section: Peripheral and Central Spatial Maps Of Ir Olfactory Sensory supporting
confidence: 88%
See 3 more Smart Citations
“…3E). These include IR75d (VL1), consistent with previous cobalt backfill analyses (Stocker et al, 1983), and the IR40a axons innervating the column but not most of the arm (Fig. 3E).…”
Section: Peripheral and Central Spatial Maps Of Ir Olfactory Sensory supporting
confidence: 88%
“…Similarly, our attempts to construct a functional reporter for IR21a, which is expressed in neurons in the arista and sacculus (Benton et al, 2009), were unsuccessful (data not shown). However, these cells may correspond to those labeled by an enhancer trap near the brivido1 gene [encoding a transient receptor potential (TRP) channel] that-consistent with previous backfill studies (Stocker et al, 1983)-project to the VP3 glomerulus at the posterior of the antennal lobe (also referred to as the proximal antennal protocerebrum) (Gallio et al, 2011). Finally, the neurons expressing two IR coreceptors, IR8a and IR25a, as well as IR76b, which is expressed in one cell in each coeloconic sensillum class (Fig.…”
Section: Peripheral and Central Spatial Maps Of Ir Olfactory Sensory supporting
confidence: 83%
See 2 more Smart Citations
“…Substantial progress has been made in understanding circuits for thermotaxis in the adult fly (3). Distinct peripheral sensory pathways for warm and cold avoidance that start in the fly antenna and project to the adult central brain, also to a region ventral to the antennal lobe, have now been identified (9,37), as well as a distinct internal sensory pathway involving the anterior cell warmth sensors in the fly brain (10). The molecules, cells, and circuits for negative thermotaxis in Drosophila larva remain poorly understood, except at noxious temperatures (18,38), and we have not yet identified circuits for negative thermotaxis (warm avoidance).…”
Section: Discussionmentioning
confidence: 99%